Lateral crural setback: an analysis on tip rotation - Langsdon, Phillip R.; Schroeder, Ronald J.; Rayess, Hani; Clinkscales, William (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Increasing nasal tip rotation is a common objective during rhinoplasty. When ptosis is either totally or partially the result of an excessive lateral crura length, strength, or position, various techniques have been used to shorten the lateral crura in order to reduce its relative inferior ptotic force. Techniques that involve division or amputation of the cartilage have been shown to be effective, but may sometimes weaken the cartilage’s shear and horizontal load strength, thus increasing the chances of unwanted sequalae in alar and/or tip contour. We presented our lateral crural setback technique as another option to allow the tip to rotate while maintaining the lateral architectural structure, end to end continuity, and horizontal load and shear strength. Methods: Retrospective review of 20 patients undergoing cosmetic rhinoplasty who had a lateral crural setback cartilage repositioning maneuver. The primary outcomes measured after one year of follow-up were nasal tip rotation and projection. Nasal tip rotation was assessed by measures of the nasolabial angle using three different methods. Results: There was a statistically significant increase in nasolabial angle using all 3 methods for measuring nasal tip rotation. The average increase in nasal tip rotation for all methods was 10.7° (p<0.0001). There was a statiscically significant decrease in tip projection. No alar distortion or complications were noted. Conclusions: The lateral crural setback technique can be used to increase nasal tip rotation while preserving the integrity of the lateral crura. No alar distortion or complications were noted from this procedure.